Influence of different positions on hemodynamics derived from noninvasive transcutaneous Doppler ultrasound. Issue 4 (20th September 2013) - Chan, Cangel Pui‐yee; Cheung, Pui‐ling; Man Tse, Mandy; Agarwal, Nandini; Narain, Sangeeta; Chan, Stewart Siu‐Wa; Smith, Brendan E.; Graham, Colin A.; Rainer, Timothy H.
Abstract A proper alignment of the ultrasound beam to the aortic or pulmonary outflow tracts is essential to acquire accurate signals. This study aimed to investigate the influence of different positions on the acquisition of Doppler signals using a noninvasive transcutaneous Doppler ultrasound. This was a prospective observational crossover study. Two operators performed hemodynamics measurements on each subject in supine, sitting, semirecumbent, passive leg raising (PLR) 20°, and PLR 60° positions using both aortic and pulmonary approaches. All Doppler flow profile images were assessed using the Fremantle and Prince of Wales Hospital criteria. Time required to obtain Doppler signals was recorded. A total of 60 subjects (50% males) aged 18–60 years old were investigated. In both sitting and semirecumbent positions, aortic stroke volume indexes (SVIs) and cardiac indexes (CIs) were significantly lower than those in the other three positions while the pulmonary CIs were comparable to that in the supine position. In the sitting position, the aortic signal qualities were lower and the time to obtain the pulmonary Doppler signals was prolonged. Instead, the signal quality and the time to obtain the Doppler signals in the semirecumbent position were similar to those in the other three positions using the pulmonary approach. PLR did not cause a significant increase in SVI regardless of the degree of leg elevation. These data show that it is feasible to perform the noninvasive transcutaneous Doppler ultrasound using the pulmonary approach in the semirecumbent position for patients unable to maintain the supine position. The aortic approach in the sitting and semirecumbent positions is not suitable as it is not sufficiently reliable.